Eurofleets +: an alliance of European marine research infrastructure to meet the evolving needs of the research and industrial communities (Marine Institute, 2022)
"EUROFLEETS+ is an H2020 project funded under the Infrastructures initiative, coordinated by the Marine Institute that brings together a significant group of key marine research actors (in particular research vessel operators) in Europe, North America and Oceania – 42 marine institutes, universities, foundations and SMEs from 24 countries."
Gesehen am 28.09.2022
Keywords: Website